A coal miner's bride : the diary of Anetka Kaminska - Bartoletti, Susan Campbell (New York : Scholastic, 2000)
A diary account of thirteen-year-old Anetka's life in Poland in 1896, immigration to America, marriage to a coal miner, widowhood, and happiness in finally finding her true love.
"Lattimer, Pennsylvania, 1896"--Cover.
800
Accelerated Reader AR
Keywords: Immigrants -- Juvenile fiction; Polish Americans -- Juvenile fiction; Coal miners -- Juvenile fiction; Diaries -- Juvenile fiction; Diaries -- Fiction; Historical fiction; Historical fiction